Isolation and preliminary characterization of a novel bacteriophage vB_KquU_φKuK6 that infects the multidrug-resistant pathogen Klebsiella quasipneumoniae - Miller, Isaac P.; Laney, Alma G.; Zahn, Geoffrey; Sheehan, Brock J.; Whitley, Kiara V.; Kuddus, Ruhul H. (Frontiers in Microbiology, 2024)
Background: Klebsiella quasipneumoniae (previously known as K. pneumoniae K6) strains are among the multidrug-resistant hypervirulent bacterial pathogens. Phage therapy can help treat infections caused by such pathogens. Here we report some aspects of virology and therapeutic potentials of vB_KquU_jKuK6, a bacteriophage that infects Klebsiella quasipneumoniae. Methods: K. quasipneumoniae (ATCC 700603) was used to screen wastewater lytic phages. The isolate vB_KquU_jKuK6 that consistently created large clear plaques was characterized using standard virological and molecular methods.Results: vB_KquU_jKuK6 has a complex capsid with an icosahedral head (~60 nm) and a slender tail (~140 nm x 10 nm). The phage has a 51% AT-rich linear dsDNA genome (51,251 bp) containing 121 open reading frames. The genome contains genes encoding spanin, endolysin, and holin proteins necessary for lytic infection and a recombinase gene possibly involved in lysogenic infection. vB_KquU_jKuK6 is stable at -80 to +67 °C, pH 4-9, and brief exposure to one volume percent of chloroform. vB_KquU_jKuK6 has a narrow host range. Its lytic infection cycle involves a latency of 20 min and a burst size of 435 plaque-forming units. The phage can cause lysogenic infection, and the resulting lysogens are resistant to lytic infection by vB_KquU_jKuK6. vB_KquU_jKuK6 reduces the host cells' ability to form biofilm but fails to eliminate that ability. vB_KquU_jKuK6 demonstrates phage-antibiotic synergy and reduces the minimum inhibitory concentration of chloramphenicol and neomycin sulfate by about 8 folds.Conclusions: vB_KquU_jKuK6 cannot be directly used for phage therapy because it is a temperate bacteriophage. However, genetically modified strains of vB_KquU_jKuK6 alone or combined with antibiotics or other lytic Klebsiella phages can have therapeutic utilities in treating K. quasipneumoniae infections.